Assessing Teacher Readiness in Early Childhood Education: An Analysis of the 2025 UM PPG Trial Question Instrument. - Aisyah, Eny Nur; Yafie, Evania; Atmoko, Adi (Universitas Pahlawan Tuanku Tambusai, 2025)
The academic readiness of PAUD teachersis an important indicator in determining their success in participating in the Teacher Professional Education (PPG). The problem that arises is the lack of comprehensive mapping regarding the level of academic readiness of PAUD teachers, particularly in the context of implementing the PPG tryout. This study aims to analyse the academic readiness of PPG PAUD participants in 2025 based on the results of a tryout participated in by 388 respondents from various regions in Indonesia. The study population consisted of all PAUD teachers who participated in the PPG UM 2025 tryout, with a sample of 388 individuals selected through total sampling. The research method employed was a descriptive, quantitative approach with frequency distribution analysis techniques. The results showed that 76 respondents (19.59%) were in the low readiness category, 256 respondents (65.98%) in the medium category, and 56 respondents (14.43%) in the high category. These findings indicate that the majority of teachers are still at the medium level of readiness, which means the a need for further academic intervention strategies. Therefore, it is recommended that institutions that organize PPG PAUD strengthen their academic provision programs, especially in the form of clinical questions, structured tutoring, and improving pedagogical and professional competencies to support a better transition towards PPG.